2012
DOI: 10.1097/id.0b013e31825fed00
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Titanium With Electrochemical Anodization on the Response of the Adherent Osteoblast-Like Cell

Abstract: The favorable biological response of SLAffinity surfaces to MG63 osteoblast-like cells suggested that electrochemical anodization after SLA treatments is a potential procedure for better osseointegration in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The higher cell viability for Porous and Vulcano at both time points indicates that rough and hydrophilic surfaces have a greater affinity with osteoblasts and hence, are more biocompatible than smooth ones. These observation is consistent with previous investigations [1, 2, 12, 13]. Cell viability over time suggests that there was a marked increase on cell proliferation rate between 3 and 7 days for Porous and Vulcano, and that their similar viability at 7 days might be due to confluence and stop on proliferation to start differentiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher cell viability for Porous and Vulcano at both time points indicates that rough and hydrophilic surfaces have a greater affinity with osteoblasts and hence, are more biocompatible than smooth ones. These observation is consistent with previous investigations [1, 2, 12, 13]. Cell viability over time suggests that there was a marked increase on cell proliferation rate between 3 and 7 days for Porous and Vulcano, and that their similar viability at 7 days might be due to confluence and stop on proliferation to start differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the extensive physical and chemical characterization of these surfaces described in the literature, in vitro biological responses to them are still not clarified. Most of the data available are related to early responses, such as cell attachment [1, 7–12], cell shape [1, 9–12], and cell proliferation [1, 2, 8, 9, 1113]. Although cell adhesion and proliferation on implant surfaces are prerequisites for the initiation of bone regeneration, the challenge in research on dental implants is the surface ability to guide the differentiation [14].…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated the cellular responses of MG63 cells cultured on SLAffinity-Ti specimens in our previous study. 6 The roughness profiles of bone-related phenotypes indicated that the SLA-Ti surfaces met the current industry standard. The rough SLA-Ti surface showed a favorable effect on osteogenic differentiation, indicating its success in clinical applications.…”
Section: Discussionmentioning
confidence: 98%
“…(Implant Dent 2014;23:659-664) Key Words: bone quality, dental implant, stress distribution, SLAffinity surface characteristics and cellular response of SLAffinity specimens also demonstrated their superior biocompatibility. [6][7][8][9][10] Treated-surface implant technology is widely used in orthopedics due to its outstanding biocompatibility with bone. However, only a few studies have investigated the interface between implant and bone because of the technological difficulties arising from the experiments.…”
mentioning
confidence: 99%
“…Recently, attention has been focused on a hybrid topography consisting of micropits and nanoporous TiO 2 layers made via electrochemical oxidation to mimic the natural bony environment. 14,15 Electrochemical oxidation had a potential to increase the wettability of the SLA (sand blasted, large grit, acid etched) surfaces, and the surfaces promoting its biocompatibility were with high wettability and a thick TiO 2 layer (SLAffinity) in the Ti-one 101 (Hung Chun Bio-S Co., Ltd, Kaohsiung, Taiwan) dental implants. Such hybrid micro/nanostructures have proven to increase hydroxyapatite (HA) formation in vitro, 16 enhance the proliferation and differentiation of osteoblasts, 14,15 and improve local factor production.…”
mentioning
confidence: 99%